2018
DOI: 10.1634/theoncologist.2017-0623
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of NETest Clinical Utility in a U.S. Registry-Based Study

Abstract: A circulating multigene molecular biomarker to guide neuroendocrine tumor (NET) management has been developed because current biomarkers have limited clinical utility. NETest is diagnostic (96%) and in real time defines the disease status (>95%) as stable or progressive. It is >90% effective in guiding treatment decisions in conjunction with diagnostic imaging. Monitoring was effective in watch-and-wait or treatment groups. Low levels supported no management change and reduced the need for imaging. High levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 34 publications
11
99
1
Order By: Relevance
“…Patients on SSA who were “responding” i.e., exhibited SD by imaging, exhibited a significantly ( p < 0.005) lower score (mean: 38) than those with image-demonstrable progression (mean score: 76). This is consistent with a recent study demonstrating that the NETest effectively identified SSA-treated patients who are responding to therapy [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Patients on SSA who were “responding” i.e., exhibited SD by imaging, exhibited a significantly ( p < 0.005) lower score (mean: 38) than those with image-demonstrable progression (mean score: 76). This is consistent with a recent study demonstrating that the NETest effectively identified SSA-treated patients who are responding to therapy [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Cost-effectiveness would be determined through changes (decreases) in imaging as has been recently noted. 46 The current study confirms that CgA has no role in predicting pNET disease recurrence. It has little accuracy, was the poorest feature for prediction and the OR (1.1) was no different to using no biomarker at all.…”
Section: Netest and Recurrence/nrsupporting
confidence: 72%
“…The frequency of testing would depend on the risk of progression. Cost‐effectiveness would be determined through changes (decreases) in imaging as has been recently noted …”
Section: Discussionmentioning
confidence: 99%
“…The NETest was 93% positive, whereas single analytes were positive in ∼40%. In 2 other independent studies, a daily clinical practice registry audit (NCT02270567) of NEN [102] and a prospective, university-based study [100] the diagnostic accuracy of the NETest was confirmed to be 95-100%. Physician confidence in using monoanalytes like CgA or pancreastatin was low (accuracy 25-50%).…”
Section: T -Primary Tumourmentioning
confidence: 92%
“…Since the multigene assay captures diverse functional "omic" components of each tumour, the assay provides a broad molecular biological characterisation of tumour behaviour. In several studies comparing the NETest with single analyte measurements for diagnosis, the NETest is superior [101][102][103] (Fig. 2).…”
Section: T -Primary Tumourmentioning
confidence: 99%